Axiology of education: Ideals and unifying values in social education of modern student youth - E. S. Sakharchuk; I. A. Kiseleva; E. R. Baghramyan; A. L. Sakharchuk (Образование и наука)
Introduction. The problem of finding axiological grounds is associated with the need to solve the tasks of implementing the progressive mission of universities in the regions. The problem appeared with sufficient evidence as a result of obtaining analytical data from the first stage of the grant study devoted to the factors of formation of students’ identity in the multi-confessional environment of the university. The data obtained testified to a pronounced individualistic focus of educational activity, which presumably could have a negative impact on the development of academic communities and cooperative forms of work at universities.Aim. The present research aims to determine the axiological foundations of the actualised educational system that corresponds to the modern interests of Russians and to clarify the ideas about the barriers that prevent the formation of university value communities on the basis of the comparison of values of students and university teachers.Methodology and research methods. The empirical basis of the study is surveys of university students and teachers. The surveys were conducted by a research group at 13 Russian universities in 2021 and 2022. Based on the description of various conceptual approaches (sociocentric, anthropocentric and theocentric) to education, theoretical and practical argumentation presented in the article, the question of the advantages and disadvantages of each of the concepts is solved. The axiometric methods used in the study (content analysis and sociometry of group preferences) made it possible to reflect the results of the analysis of a significant sample (1,256 students and 87 teachers were interviewed). The analysis differs from the well-known studies of recent years also in temporal characteristics (specific time points were selected to trace to a certain extent the dynamics of value orientations due to the sociocultural specifics of the historical moment).Results. The nature of the modern postmodern ideology of education is clarified. It is revealed that its priorities are associated with individualistic orientations, coupled with egocentric interests, which represent the idea of eternal values and public benefit on the periphery. The ideology of postmodern pedagogy is contrasted with the value-semantic principles of the traditional culture of education, focused on the growth of the social personality, characterised by a formalised idea of the ideal. The sociocentric approach emphasises the need for subject-subject interaction taking into consideration the question of the idea of the ideal is significant for all participants in the educational process.Scientific novelty. The scientific novelty of the research lies in the analytical results obtained, indicating signs of agnosticism and spiritual passivity of students, hedonistic dominants and general confusion in determining the semantic priorities of modern students, on the one hand, and the insufficiently realised role of teachers as mentors, personally transmitting positive spiritual and value experience, on the other. Along with the problem of educating students and correcting their attitude tothe teacher, the question of the need for the formation of socially significant ideals-oriented thinking of teachers is raised.Practical significance. The observations and conclusions may be of interest in the development of managerial and coordinating recommendations in professional and higher education.